2008
DOI: 10.1590/s0047-20852008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de mulheres usuárias de álcool em ambulatório especializado em dependência química

Abstract: Embora cresça o número de mulheres com abuso ou dependência alcoólica, elas ainda permanecem como alvo não prioritário na tomada de decisão dos gestores de políticas públicas. OBJETIVOS: Caracterizar o perfil sociodemográfico de mulheres com abuso ou dependência do álcool, identificar o consumo alcoólico, as intervenções terapêuticas realizadas e alguns fatores que poderiam estar relacionados ao abandono precoce do tratamento nesta população. METÓDOS: Foram incluídas 192 mulheres que procuraram pela primeira v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
20

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 22 publications
2
21
0
20
Order By: Relevance
“…18 A Brazilian study of female alcohol users treated at a specialized outpatient clinic showed that most of them presented severe dependence. 19 The mean age of our sample is in line with the relevant literature, which shows that substance abusers tend to seek treatment later in life than individuals with other psychiatric disorders, probably as a result of a higher number of barriers to treatment initiation. 7 In turn, the higher mean age observed in our patients when compared with samples of non-alcohol drug users may be explained by the high rates of alcohol use and abuse observed in our study, as problems alcohol-related problems tend to manifest later in life.…”
Section: Ethical Considerationssupporting
confidence: 86%
See 1 more Smart Citation
“…18 A Brazilian study of female alcohol users treated at a specialized outpatient clinic showed that most of them presented severe dependence. 19 The mean age of our sample is in line with the relevant literature, which shows that substance abusers tend to seek treatment later in life than individuals with other psychiatric disorders, probably as a result of a higher number of barriers to treatment initiation. 7 In turn, the higher mean age observed in our patients when compared with samples of non-alcohol drug users may be explained by the high rates of alcohol use and abuse observed in our study, as problems alcohol-related problems tend to manifest later in life.…”
Section: Ethical Considerationssupporting
confidence: 86%
“…50 Another study assessing a population of female drug users undergoing psychiatric treatment in São Paulo showed that representations on the use of alcohol in these women were linked to family, profession and gender issues, indicating that the search for treatment was not only motivated by substance use per se, but by all areas affected by such use.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…O tempo de espera entre diferentes etapas do tratamento, como o intervalo entre a entrevista inicial e o primeiro atendimento, influencia no aumento da evasão e a diminuição desse intervalo é uma estratégia para melhorar o programa de intervenção 15 . A literatura encontrada aponta que mais que 50% dos pacientes evadem-se no primeiro mês 16 . Desse modo, o período inicial é um momento crítico para a permanência desses pacientes.…”
Section: ▄ Discussãounclassified
“…A associação observada entre o consumo de álcool e a cor das mulheres ressaltando a maior prevalência entre as que se autoclassificaram brancas é reafirmado em estudos presentes na literatura (19)(20) . No entanto, a relação entre tais variáveis ainda não está clara na literatura disponível; sabe-se que as pessoas negras e pardas tendem a estarem mais vulneráveis em termos econômicos (21) e que as pessoas com maior poder aquisitivo estão mais vulneráveis ao consumo de substâncias, pois existe mais disponibilidade financeira para se gastar com bebidas, ou ainda, que seu uso esteja ligado ao status social, acesso facilitado e menores restrições sociais (20,22) , logo, o fator renda poderia explicar tal correlação.…”
Section: Discussionunclassified